MATERIAL MANAGEMENT AND SUSTAINABILITY OF COUNTY CONSTRUCTION PROJECTS IN GARISSA COUNTY, KENYA - Ibrahim, Abdi Abdikadir; Kirui, Mr. Caleb (International Journal of Project Management, 2017)
Purpose: The purpose of the study was to assess the effect of material management on the sustainability of construction projects in Garissa County. Methodology: The study used a descriptive survey research design. The target population under study comprised of 200 construction projects in Garissa County. This study took 30% of the target population and thus 60 construction projects which was used for the study. Stratified random sampling technique was used to select the 60 construction projects. The study will consider 3 permanent staff from each construction project (Top Management, middle management and operational staff) as they provided informative details concerning the research. Therefore the total respondents were 180 (60*3). Results: The study found out that procurement and purchasing processes and sustainability are positively and significantly related(r=0.288, p=0.000), Reduce, Reuse, and Recycle and sustainability are positively and significantly related (r=0.291, p=0.000). It was further established that material cost and sustainability are negatively and significantly related (r=-0.119, p=0.001).Similarly, results showed that energy saving practices and sustainability are positively and significantly related (r=0.083, p=0.000). Unique contribution to theory, practice and policy: Based on the research findings, the study recommended for the projects construction management to order materials in the right quantities and material handling should be such as to minimize waste on site.